5x+4x-20=62-(x+2)

Simple and best practice solution for 5x+4x-20=62-(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+4x-20=62-(x+2) equation:


Simplifying
5x + 4x + -20 = 62 + -1(x + 2)

Reorder the terms:
-20 + 5x + 4x = 62 + -1(x + 2)

Combine like terms: 5x + 4x = 9x
-20 + 9x = 62 + -1(x + 2)

Reorder the terms:
-20 + 9x = 62 + -1(2 + x)
-20 + 9x = 62 + (2 * -1 + x * -1)
-20 + 9x = 62 + (-2 + -1x)

Combine like terms: 62 + -2 = 60
-20 + 9x = 60 + -1x

Solving
-20 + 9x = 60 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-20 + 9x + x = 60 + -1x + x

Combine like terms: 9x + x = 10x
-20 + 10x = 60 + -1x + x

Combine like terms: -1x + x = 0
-20 + 10x = 60 + 0
-20 + 10x = 60

Add '20' to each side of the equation.
-20 + 20 + 10x = 60 + 20

Combine like terms: -20 + 20 = 0
0 + 10x = 60 + 20
10x = 60 + 20

Combine like terms: 60 + 20 = 80
10x = 80

Divide each side by '10'.
x = 8

Simplifying
x = 8

See similar equations:

| 5x+4(x-20)=62-x+2 | | 6-19=7x-8-6x | | 64a^2-81p^2= | | 14x-6y=30 | | 20x^2+13x-15=0 | | 1(3-x)=1-(x-2) | | 3x^2-x-48=-16 | | 2w^2+1w=45 | | 9q+5-2p=0 | | y-0.9y=4350 | | -3(4s-5)-15=-3(8s+2)-4 | | (5x+4)(x-20)=62-(x+2) | | 12x-6=0 | | 3x^2-6x+1= | | 24x^2-180x-96=0 | | 12(2x^2-15x-8)=0 | | 9b^2+24b+16=0 | | 2x^2+60y+162= | | 2=4-x | | 2=4-6 | | 4x-10=2x-2 | | 49w^2-16f^2=0 | | 4-x=-7 | | 4b^2+28bd+49d^2=0 | | 49m^2-112m+64=0 | | 4w^2+28w+49t^2= | | 7x+4=5-(4x-4) | | -7=2x+5 | | 25s-30s+9= | | m(19m+9)=10 | | (A+6)+(B+6)=C+6 | | 8n-(-2)/7=6 |

Equations solver categories